Purification of Aqueous Solutions from Chromium Using Glass Sand - Mohammed, Mohammed I.; Awadh, Salih M. (Iraqi Journal of Science, 2025)
This study aims to determine the ability of glass sand to absorb chromium from aqueous solutions. Glass sand samples were collected from the Rutba Formation (Cenomanian age) in the Western Desert of Iraq. Numerous laboratory experiments were conducted to test the effects of time and concentration on adsorption. For a duration of 5, 10, 15, 20, 25, 30, 35, 40, 45, and 50 minutes, four initial chromium concentrations (20, 40, 60, and 80) were tested. Glass sand to chromium solution ratio was 2 grams to 30 ml. Total dissolved solids (TDS), electrical conductivity (EC), and pH values were measured at 30ºC. The equilibrium time is determined as 20 min in most concentrations. The equation of Freundlich showed that the adsorption intensity (n) is equal to 0.0603, the constant of the Freundlich equation (Kf) = 59.06, Langmuir equation showed the sorption capacity (Qo) equivalent to 1.0989 mg/g, (KL) is 0.0487. The absorption of chromium was modelled using both the Langmuir and Freundlich equations. It was discovered that glass sand had the highest efficiency in chromium adsorption for solutions with a concentration of 20, reaching 74.54, and clarified how glass sand material could benefit from reducing the chromium concentrations from aqueous solutions protecting the environment.